ESG Risk Determinant Factors: Study on Indonesia Listed Firm - Maulana, Ilham (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2023)
Companies worldwide are now looking at long-term and sustainable development in environmental, social, and governance issues in addition to short-term earnings. This paradigm change occurred in Indonesia as well. Companies listed on the Indonesian stock exchange are increasingly vying to establish sustainable operations because they understand the value of ESG considerations. However, what is the factors that determine the ESG risk rating? The purpose of this research is to determine what factors influence ESG risk. Based on the data that has been obtained, the researchers tested the data using PLS-SEM with Warppls 8.0. Then the following results were obtained: institutional investor structure has a negative effect on ESG risk; firm performance, firm size, and leverage have a positive influence on ESG risk; and lastly, firm performance can be a moderating variable of the relationship between institutional investor structure and ESG risk.